(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
Blessing and curse phrases constitute an important layer of expressive and evaluative language, reflecting speakers’ emotional attitudes and cultural values. This article examines the synonymic peculiarities of blessing and curse phrases in English and Uzbek, focusing on semantic proximity, functional equivalence, and structural variation. The study identifies core synonymic groups, analyzes their semantic intensity and stylistic coloring, and highlights both universal and language-specific features. The findings demonstrate that synonymy in blessing and curse phrases is shaped not only by lexical meaning but also by cultural norms, pragmatics, and ritual usage.